Perancangan Software Interface pengendalian Lampu Lalu Lintas Simpang Lima Berbasis Mikrokontroller Atmega 8535 - Rambe, Mulia Sakti; Marpaung, Noveri Lysbetti; Amri, Rahyul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Design software interface controlling traffic light intersection ATMega8535 five-basic microcontroller is design to facilitate operator traffic light. This software design involves two different software,software Visual Basic 6.0 and CodeVision avr, Visual Basic 6.0 as a software interface that will send data and CodeVision avr as recipient of the data that is in its hardware. Sending and receiving data here using the existing serial port in komputere that use serial usb rs232 which serves to connect or bridge the respective software sendiri.Pengiriman data through the interface that Visual Basic 6.0, this shipment using the DO pin as data transmission (RX) which in usb serial and in ATMega8535 and received using D1 pin that serves as a data receiver (TX) .Each pin is connected using the USB serial rs232. This method allows an operator to use and change the time when need it. Because the software interface gives the ease of service at rush hour or operarator like solid hours already available, and only enter a number already there dikolom disediakan.Perpindahan in this column automatically, and a solid hour or busy can also be arranged according to the wishes of the operator.Keywords: interface, microcontroller ATMega8535, usb serial